2003
DOI: 10.1109/tmtt.2003.808704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baseband impedance on FET intermodulation

Abstract: The intermodulation performance of an FET in the common-source configuration is dependent on the impedance presented to its gate and drain terminals, not only at fundamental, but also at harmonic and baseband frequencies. At baseband frequencies, these terminating impedances are usually determined by the bias networks, which may have varying impedance over the frequencies involved. This can give rise to asymmetry in two-tone intermodulation levels, and changing intermodulation levels with tone spacing, as prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 13 publications
(17 reference statements)
4
46
0
2
Order By: Relevance
“…The dips of Figure 9 are now peaks of IMD, more noticeable as input power increases. This result is fully consistent with the work reported in [2,3], concerning the analysis of IMD by using series expansions up to third order of the device nonlinearities. Besides, it was demonstrated that the variation of the IMD with the drain impedance could be inverted in sign, and even neglected, with an accurate bias point selection.…”
Section: Influence Of the Bias Pointsupporting
confidence: 92%
See 2 more Smart Citations
“…The dips of Figure 9 are now peaks of IMD, more noticeable as input power increases. This result is fully consistent with the work reported in [2,3], concerning the analysis of IMD by using series expansions up to third order of the device nonlinearities. Besides, it was demonstrated that the variation of the IMD with the drain impedance could be inverted in sign, and even neglected, with an accurate bias point selection.…”
Section: Influence Of the Bias Pointsupporting
confidence: 92%
“…Nevertheless, no imbalance can be detected between lower and upper IMD components. This result is fully coherent with those stated before [2,3,11,12], because imaginary parts of impedance at fundamental and second harmonic bands are close to zero. …”
Section: A Influence Of the Bias Networksupporting
confidence: 92%
See 1 more Smart Citation
“…Continuous Wave (CW) waveform measurement and engineering has established itself as a highly effective design solution for the development of power amplifiers [7][8] [9]. However, modern modulation schemes such as CDMA and OFDM demand characterisation over extended instantaneous bandwidths of up to 100 MHz.…”
Section: Modulated Waveform Measurement Systemmentioning
confidence: 99%
“…6). Bandwidth dependent memory effects [17] are determined through proper selection of the values of the corresponding LPFs' parameters listed in Table I. For wider two-tone spacings, and with the appropriate selection of the low pass filters' parameters (as discussed in previous paragraph), the model can still capture bandwidth dependent memory effects.…”
Section: Model Extraction and Experimental Validationmentioning
confidence: 99%